Childhood Years : A Memoir - Tanizaki, Jun'ichirō, 1886-1965 (Michigan monograph series in Japanese studies ;, 2017)
In Childhood Years, originally published serially in a literary magazine between 1955 and 1956, Tanizaki Jun'ichiro (1886-1965) takes a meandering look back on his early life in Tokyo. He reflects on his upbringing, family, and the capital city with a conversational--and not necessarily honest--eye, offering insights into his later life and his writing.